Performance Audit of Integrated Child Development Services (ICDS) Scheme - CAG of India (CAG of India, 2012)
The Integrated Child Development Services (ICDS) scheme was launched as a centrally sponsored scheme on 2nd October 1975. About a decade ago, CAG of India's audit report on ICDS (Report No 3 of 2000 (Civil)) had revealed that the policy of universalisation of ICDS scheme remained unattained and the scheme could not achieve the desired goals. In that performance audit, CAG of India had also reported that the Supplementary Nutrition (SN) component had failed to improve the health status of beneficiaries, implementation of the component of health check-up and referral services was found deficient and due to non-fixation of targets and absence of monitoring mechanism, full coverage under immunisation could not be assured besides many other findings. Thus, CAG of India decided to conducted a follow up audit to assess the current status of ICDS scheme, and also whether the issues highlighted in earlier report had been appropriately addressed.
For the Period 2006-07 to 2010-11